Clinicopathological Differences and Prognostic Value of Hypoxia-Inducible Factor-2α Expression for Gastric Cancer: Evidence From Meta-Analysis. Issue 7 (February 2016) - Zheng, Fangchao; Du, Feng; Zhao, Jiuda
Abstract : Abstract: Published literatures have reported the relationship between hypoxic-inducible factor-2α (HIF-2α) expression and clinicopathological features in gastric cancer (GC), but the evaluated conclusions remain controversial. A meta-analysis was carried to examine the clinicopathological features and prognostic values of HIF-2α in patients with GC. Systematic detailed searches were performed to Pub Med, Cochrane Library, and EBSCO until to August 2015. Six studies (508 specimens) were included in this meta-analysis. HIF-2α-positive expression indicates an unfavorable prognosis value and advanced clinicopathological differences for the available patient dates with GC. Further multivariate meta-analysis revealed that HIF-2α-positive expression in gastric cancer associated with deeper tumor infiltration (OR = 3.08; 95%CI: 1.18–8.04), higher rates of lymphatic metastasis (OR = 3.26; 95%CI: 1.10–9.63), higher TNM stage (III+IV) (OR = 2.61; 95%CI: 1.40–4.84), and much lower 5-year overall survival (OR = 2.08; 95%CI: 1.21–3.58). Nevertheless, there is no association between HIF-2α-positive expression and worse tumor differentiation (OR = 2.03; 95%CI: 0.73–5.64). In addition, by this subgroup analysis, HIF-2α-positive expression associated with deeper tumor infiltration (OR = 3.81; 95%CI: 1.03–14.08), higher lymphatic metastasis (OR = 4.71; 95%CI: 1.08–20.50), higher TNM stage (OR = 3.21; 95%CI: 1.57–6.57), worse tumor differentiation (OR = 3.08; 95%CI: 1.51–6.31), and lower 5-year overall survival (OR = 2.34; 95%CI: 1.15–4.79). Our results indicate that HIF-2α overexpression can potently predict the poor prognosis and may be a potential therapeutic target for gastric carcinoma, according to the limited evidence. Meanwhile, further studies are needed to elucidate the accuracy of these results.